ABC of quality improvement in healthcare - Swanwick, Tim; Vaux, Emma (Hoboken : Wiley-Blackwell, 2020)
'Quality improvement (QI) is embedded in the fabric of successful healthcare organisations across the world, with healthcare professionals increasingly expected to develop and lead improvement as a core part of their clinical responsibilities. As a result, QI is rapidly becoming a feature of the education and training programmes of all healthcare professionals. Written and edited by some of the leading clinicians and managers in the field, ABC of Quality Improvement is designed for clinicians new to the discipline, as well as experienced leaders of change and improvement. Providing comprehensive coverage and clear, succinct descriptions of the major tools, techniques and approaches, this new addition to the ABC series demystifies quality improvement and develops a broader understanding of what constitutes quality in healthcare. With practical examples of improvement interventions and the common pitfalls that can befall them, this book will support and enable readers to manage change projects within their own organisations. Relevant to doctors, dentists, nurses, health service managers and support staff, medical students and doctors in training, their tutors and trainers, and other healthcare professionals at various levels, ABC of Quality Improvement will give readers the confidence to embark on their own improvement projects, whoever, and wherever they may be'--
Includes bibliographical references and index.
Keywords: Quality Assurance, Health Care; Quality Improvement